The Perspective of ‘Urf on the Implementation of the Ba Iyeh Tradition in Marriage Customs in Padang Pariaman Regency - Aidha Febriani; Firdaus Firdaus; Zainal Azwar (Darul Yasin Al Sys, 2026)
Local marriage traditions continue to shape the relationship between customary practice, religious belief, and community identity in Minangkabau society. However, research specifically examining the Ba Iyeh tradition in Nagari Tapakih from the perspective of ‘urf remains limited. This study aims to analyze the implementation of Ba Iyeh in marriage customs and examine its position within Islamic legal reasoning through the concept of ‘urf. An empirical qualitative approach with field research was employed, involving religious leaders, customary leaders, and community members selected through purposive sampling. Data were collected through interviews and documentation and analyzed using descriptive qualitative analysis based on the concept of ‘urf. The findings indicate that Ba Iyeh begins with mandi balimau or mandi kembang, followed by incense smoke, the application of pauweah, mantra recitation, symbolic hair cutting near the crown of the head, and doa paga diri before the bride or groom wears wedding attire. From the perspective of ‘urf, this tradition is categorized as ‘urf al-‘amalī and ‘urf al-khāṣ. However, it may become ‘urf fāsid when it contains superstition, mystical claims, or elements contrary to sharia. The study concludes that Ba Iyeh reflects the dynamic interaction between Minangkabau customary practice and Islamic legal norms. These findings contribute to the study of Islamic customary law and provide practical implications for customary and religious leaders to reconstruct the tradition by preserving its cultural values while eliminating elements that conflict with Islamic teachings.